Reactions of 1, 1-Bismethylthio-2-nitroethylene. IV. Syntheses and Reactions of 4-Methylthio-2-buten-4-olide Derivatives - SONE, MASAKATSU; MATSUDA, YOSHIRO; TOMINAGA, YOSHINORI; KOBAYASHI, GORO; NATSUKI, REIKO (Chemical & pharmaceutical bulletin, 1974)
Treatment of methyl 2-cyano-3-methylthio-4-nitrocrotonate with conc. sulfuric acid gave 2-carbamoyl-3-methylthio-2-buten-4-olide (II) in a good yield. This compound (II) was formed easily by the replacement reaction between methylthio group and nucleophilic reagents such as amines or active methylene compounds. Condensation reaction of II as a nucleophilic reagent with various reagents having a formyl or ketone group gave corresponding condensation products. Reaction of II with quinoline 1-oxide gave 2-carbamoyl-3-methylthio-4, 4-bis (2-quinolyl)-2-buten-4-olide (X).